A stroboscopic averaging algorithm for highly oscillatory delay problems. (13th April 2018) - Sanz-Serna, J M; Zhu, Beibei
Abstract: We propose and analyse a heterogeneous multiscale method for the efficient integration of constant-delay differential equations subject to fast periodic forcing. The stroboscopic averaging method suggested here may provide approximations with O(H^2+1/^2) errors with a computational effort that grows like H^-1 (the inverse of the step size), uniformly in the forcing frequency .